A TiN / SiC composite ceramic material and preparation method thereof
By introducing TiN/SiC composite ceramic material into the silicon carbide ceramic matrix, high-strength TiN grains and SiC are generated by carbon-thermal reduction nitriding and reactive permeation methods, the problem of excessive brittleness of reactive sintered silicon carbide ceramic materials is solved, and the material is enhanced toughening and efficient preparation is achieved.
Patent Information
- Application Number
- CN202411976351.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The brittleness of the reactive sintered silicon carbide ceramic materials is too high, has low toughness, and is prone to brittle fracture, which limits its wide application in the field of high-tech.
By introducing TiN/SiC composite ceramic material into the silicon carbide ceramic matrix, carbon thermal reduction and nitriding of titanium dioxide powder and carbon black under a nitrogen atmosphere, uniformly distributed high-strength TiN grains are generated, and the molten Si and carbon black react to form SiC through reaction and permeation, so as to achieve reaction sintering of the ceramic material.
It effectively enhances the strength and toughness of TiN/SiC composite ceramic materials, improves the preparation efficiency of the material, and achieves enhanced toughening of the reacted sintered silicon carbide ceramics through a diffusion strengthening mechanism.
Smart Images

Figure CN119775046A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of reaction-sintered silicon carbide ceramic preparation, and in particular to a TiN / SiC composite ceramic material and a preparation method thereof. Background Art
[0002] The process flow of preparing silicon carbide ceramics by reaction sintering mainly includes: mixing silicon carbide powder, carbon powder and binder, sintering, drying, debinding and siliconizing to obtain reaction sintered silicon carbide ceramics. The reaction sintering preparation technology has the characteristics of simple process, low sintering temperature, short time, and can achieve net size sintering. Its ceramic products have broad application prospects in high-tech fields such as aerospace, high-temperature structural parts and wear-resistant components.
[0003] However, the application of reaction-sintered silicon carbide ceramics is mainly limited by its excessive brittleness and low toughness. Brittle fracture is prone to occur during application, resulting in material damage. The main solutions to this defect currently include particle dispersion toughening, fiber toughening and phase change toughening. Among them, particle dispersion toughening is to introduce second-phase particles into the silicon carbide ceramic matrix and make them dispersed, thereby playing a toughening role. In this toughening mechanism, the intrinsic strength of the second-phase particles and the uniformity of their dispersion distribution are the main factors affecting their toughening effect. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a TiN / SiC composite ceramic material and a preparation method thereof. The present invention can prepare an effectively reinforced and toughened TiN / SiC composite ceramic material with simple preparation and high efficiency.
[0005] The present invention provides a method for preparing a TiN / SiC composite ceramic material, comprising the following steps:
[0006] Step 1: Mix silicon carbide powder, carbon black, titanium dioxide powder, a binder and water to obtain a slurry; the mass ratio of the silicon carbide powder, carbon black and titanium dioxide powder is 45-65:25-35:10-20;
[0007] Step 2, placing the slurry in a mold and letting it stand, drying it, and demolding it to obtain a porous ceramic body;
[0008] Step 3: burying the porous ceramic body with silicon powder, and performing carbon thermal reduction nitridation at 1300-1500° C. in a flowing nitrogen atmosphere to obtain a TiN / SiC / C porous ceramic preform;
[0009] Step 4: The TiN / SiC / C porous ceramic preform is kept at a temperature of 1600-1750° C. and a vacuum degree of 1-30 Pa to obtain a TiN / SiC composite ceramic material.
[0010] The method for preparing the reaction-sintered silicon carbide ceramic material provided by the embodiment of the present invention has a simple process and is easy to control; it mainly generates uniformly distributed high-strength TiN grains in situ in the porous ceramic body by carbon thermal reduction nitridation of titanium dioxide powder and carbon black in a nitrogen atmosphere, and then reacts molten Si with carbon black to generate SiC by reaction infiltration to achieve reaction sintering of the ceramic material. The excess of carbon black is controlled to ensure the complete reaction of titanium dioxide and serve as a carbon source for reaction infiltration. The TiN / SiC composite ceramic material is prepared in one step by combining carbon thermal reduction nitridation with reaction infiltration, which improves the preparation efficiency of the material and realizes the enhancement and toughening of the reaction-sintered silicon carbide ceramic through the dispersion strengthening mechanism.
[0011] In a specific embodiment of the present invention, 45-65wt% of silicon carbide powder, 25-35wt% of carbon black and 10-20wt% of titanium dioxide powder are used as powder raw materials. The three powders can be ball-milled for 1-3h to make them fully mixed; preferably, the ball-milled powder raw materials are placed in a stirring tank, 1-5wt% of a binder in an amount of 1-5wt% of the total weight of the powder raw materials, and 1-5wt% of a dispersant in an amount of 1-5wt% of the total weight of the powder raw materials are added, and then 80%-100% of water in an amount of the total weight of the powder raw materials is added thereto, and stirring can be continued for 30-60min to obtain a slurry.
[0012] Preferably, the purity of the silicon carbide powder is 85% or more, specifically 85-99.9%, and is a commercially available product; the particle size of the silicon carbide powder is preferably 5-40 μm, further 10-40 μm. Preferably, the purity of the titanium dioxide powder is 90% or more, specifically 90-99.9%, and is a commercially available product, and its particle size may be 1-10 μm.
[0013] Preferably, the carbon black has a particle size of 1 to 20 μm and a purity of more than 95%, and is a commercially available product. The mass ratio of the silicon carbide powder, carbon black and titanium dioxide powder is 45 to 65: 25 to 35: 10 to 20; further 45 to 65: 25 to 30: 10 to 20, for example 60: 25: 15, 50: 30: 20, etc. The embodiment of the present invention mainly uses excess carbon black, which is conducive to the complete reaction of titanium dioxide and serves as a carbon source for subsequent reaction infiltration.
[0014] Preferably, the binder is sodium hydroxymethylcellulose and / or hydroxyethylcellulose. Preferably, the mass of the binder is 1-5%, further 2-5%, of the total mass of silicon carbide powder, carbon black and titanium dioxide powder.
[0015] Furthermore, the slurry preferably also contains a dispersant to facilitate the slurry to be dispersed and stabilized; the dispersant may be one or more of ethanol, methylpentanol, polyethylene glycol and fatty acid polyethylene glycol ester, preferably ethanol or methylpentanol. Preferably, the mass of the dispersant is 1 to 5% of the total mass of silicon carbide powder, carbon black and titanium dioxide powder. The polymers in the dispersant are all commonly used additives in the art, and there is no special restriction on their molecular weight. In addition, the water is generally deionized water.
[0016] Preferably, in the step 1, the silicon carbide powder, carbon black and titanium dioxide powder are first ball-milled and mixed, and then a binder, a dispersant and water are added and conventionally stirred and mixed to obtain a uniformly mixed slurry.
[0017] In the embodiment of the present invention, the prepared slurry can be poured into a mold, left to stand for a certain period of time, preferably freeze-dried or forced-dried for 24 hours, and demolded to obtain a porous ceramic body.
[0018] Preferably, in step 2, the standing time is 7 to 9 hours, and further 8 hours; the drying is freeze drying or forced air drying, and the specific operating conditions are well known to those skilled in the art and are not particularly limited. In addition, the present invention also has no particular restrictions on the mold.
[0019] Preferably, in the step three, the amount of silicon powder used is twice the weight of the porous ceramic green body; and the time of the carbon thermal reduction nitridation is 2 to 10 hours.
[0020] Specifically, the embodiment of the present invention weighs the same weight of silicon powder as the porous ceramic body, pours it into a graphite crucible and spreads it, places the porous ceramic body on the spread silicon powder, and then weighs the same weight of silicon powder and spreads it on the porous ceramic body so that it is buried in the silicon powder; puts the graphite crucible into a vacuum carbon tube furnace, opens the air inlet valve and the exhaust valve, and heats it to 1300-1500°C, preferably 1350-1500°C, more preferably 1450-1500°C in a flowing nitrogen atmosphere, and keeps it warm for 2-10 hours to obtain a TiN / SiC / C porous ceramic preform by carbon thermal reduction nitridation. Among them, the silicon powder is a powder with conventional performance in this field; there is no restriction on the shape of the body, and there is no special restriction on the nitrogen flow rate, which can be adjusted according to the reaction adaptability.
[0021] After the insulation is completed, the air inlet valve and the exhaust valve are closed. In a specific embodiment of the present invention, the vacuum valve and the vacuum pump are opened to maintain the vacuum degree in the carbon tube furnace at 1-30 Pa, and the temperature is raised to 1600-1750° C., and vacuum insulation is performed to react molten Si with carbon black to generate SiC through reactive infiltration, thereby realizing reactive sintering of the ceramic material; after the insulation is completed, the furnace is naturally cooled to obtain a TiN / SiC composite ceramic material.
[0022] Preferably, in step 4, the heat preservation time is 30 to 120 minutes, and further 60 to 120 minutes; and then the mixture can be cooled naturally to obtain a TiN / SiC composite ceramic material.
[0023] Accordingly, the present invention provides a TiN / SiC composite ceramic material obtained by the preparation method as described above; high-strength TiN grains are evenly distributed in the SiC matrix, and the material has good strength, toughness, etc.
[0024] The present invention selects silicon carbide powder, carbon black and titanium dioxide powder as main raw materials, mixes them in proportion to form slurry, and then forms a porous ceramic body by statically placing it in a mold, and then buries it with silicon powder. In a flowing nitrogen atmosphere, carbon thermal reduction nitridation is performed at 1300-1500° C. to obtain a TiN / SiC / C porous ceramic preform. Finally, at a temperature of 1600-1750° C., a vacuum degree of 1-30 Pa is maintained, and the heat is kept to obtain a TiN / SiC composite ceramic material. The present invention uses carbon thermal reduction nitridation of titanium dioxide powder and carbon black in a nitrogen atmosphere to in-situ generate uniformly distributed high-strength TiN grains in a porous ceramic body, and then uses reactive infiltration to react molten Si with carbon black to generate SiC to achieve reactive sintering of the ceramic material; wherein the excess carbon black can ensure the complete reaction of titanium dioxide and serve as a carbon source for reactive infiltration, and a TiN / SiC composite ceramic is prepared by a one-step method combining carbon thermal reduction nitridation and reactive infiltration, which has a simple process, is easy to control the process, and improves the preparation efficiency of the material, and the uniformly distributed high-strength TiN grains also achieve reinforcement and toughening of the reactive sintered silicon carbide ceramic through a dispersion strengthening mechanism. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention or the core of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings under the premise of continuous creative work.
[0026] Figure 1 The XRD pattern of TiN / C composite porous ceramics prepared by carbothermal reduction nitridation is explored before the implementation of the present invention;
[0027] Figure 2 This is an SEM image of TiN / C composite porous ceramics prepared by carbon thermal reduction nitridation before the implementation of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those skilled in the art generally understand. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the various reagents and raw materials used in the present invention are all commodities that can be purchased from the market or products that can be prepared by recognized methods, and material sample testing is carried out according to national standard methods.
[0029] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0030] Example 1
[0031] In the following examples, the steps of the TiN / SiC composite ceramic and the preparation method thereof include:
[0032] Step 1, using 65wt% of silicon carbide powder, 35wt% of carbon black and 10wt% of titanium dioxide powder as powder raw materials, ball-milling the silicon carbide powder, titanium dioxide powder and carbon black for 3h to fully mix them, placing the ball-milled powder raw materials in a stirring tank, adding 5wt% of a binder and 1wt% of a dispersant based on the total weight of the powder raw materials, and then adding 100% of deionized water based on the total weight of the powder raw materials, and continuously stirring for 60min to obtain a slurry;
[0033] Step 2: pour the obtained slurry into a mold, let it stand for 8 hours, freeze-dry it for 24 hours, and demold it to obtain a porous ceramic body;
[0034] Step three, weigh the same weight of silicon powder as the porous ceramic body, pour it into a graphite crucible and spread it, place the porous ceramic body on the spread silicon powder, and then weigh the same weight of silicon powder and spread it flat on the porous ceramic body, so that the porous ceramic body is buried in the silicon powder; put the graphite crucible into a vacuum carbon tube furnace, open the air inlet valve and the exhaust valve, raise the temperature to 1300°C in a flowing nitrogen atmosphere, and keep it warm for 2 hours.
[0035] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 30Pa, heat to 1600°C, and keep warm for 120 minutes. After the insulation is completed, cool naturally to obtain the TiN / SiC composite ceramic material.
[0036] The purity of silicon carbide powder is 95% and the particle size is 5 μm. The purity of titanium dioxide powder is 99% and the particle size is 5 μm. The purity of carbon black is 98% and the particle size is 15 μm. The binder is sodium hydroxymethyl cellulose and the dispersant is polyethylene glycol.
[0037] The bending strength of the TiN / SiC composite ceramics is 352MPa and the fracture toughness is 4.3MPa·m 1 / 2 .
[0038] Example 2
[0039] The same as Example 1, the only difference is that the carbon thermal reduction temperature in nitrogen atmosphere is 1400°C. The bending strength of the prepared TiN / SiC composite ceramic is 346MPa, and the fracture toughness is 4.1MPa·m 1 / 2 .
[0040] Example 3
[0041] The same as Example 1, the only difference is that the vacuum reaction infiltration temperature is 1700°C. The bending strength of the TiN / SiC composite ceramic is 338MPa, and the fracture toughness is 4.5MPa·m 1 / 2 .
[0042] Figure 1 Before the implementation of the present invention, the X-ray diffraction (XRD) diagram of the TiN / C composite porous ceramic prepared by carbon thermal reduction nitridation at 1400°C was explored. Analysis showed that titanium dioxide was converted into TiN and a small amount of C remained, which can be used as a carbon source for vacuum reactive infiltration.
[0043] Figure 2 The SEM (scanning electron microscope) image of the TiN / C composite porous ceramic prepared by carbon thermal reduction at 1400°C was explored before the implementation of the present invention. Analysis shows that the TiN / C grains and pores in the porous ceramics prepared by the preparation process of the present invention are evenly distributed, which is beneficial to the contact and reaction of the silicon source infiltration with C in the subsequent vacuum reactive infiltration. The evenly distributed TiN grains are also beneficial to the realization of dispersion strengthening of the second phase grains.
[0044] Example 4
[0045] Step 1, using 60wt% of silicon carbide powder, 25wt% of carbon black and 15wt% of titanium dioxide powder as powder raw materials, ball-milling the silicon carbide powder, titanium dioxide powder and carbon black for 3h to fully mix them, placing the ball-milled powder raw materials in a stirring tank, adding 3wt% of a binder and 3wt% of a dispersant based on the total weight of the powder raw materials, and then adding 80% of deionized water based on the total weight of the powder raw materials, and continuously stirring for 45min to obtain a slurry;
[0046] Step 2: pour the obtained ceramic slurry into a mold, let it stand for 8 hours, freeze-dry it for 24 hours, and demold it to obtain a porous ceramic body;
[0047] Step 3, weighing the same weight of silicon powder as the porous ceramic body, pouring it into a graphite crucible and spreading it, placing the porous ceramic body on the spread silicon powder, and then weighing the same weight of silicon powder and spreading it on the porous ceramic body, so that the porous ceramic body is buried in the silicon powder; placing the graphite crucible in a vacuum carbon tube furnace, opening the air inlet valve and the exhaust valve, heating to 1400° C. in a flowing nitrogen atmosphere, and keeping it warm for 5 hours;
[0048] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 20Pa, heat to 1700°C, and keep warm for 60 minutes. After the insulation is completed, cool naturally to obtain the TiN / SiC composite ceramic material.
[0049] The purity of the silicon carbide powder is 99% and the particle size is 40 μm. The purity of the titanium dioxide powder is 96% and the particle size is 3 μm. The purity of the carbon black is 99% and the particle size is 20 μm. The binder is hydroxyethyl cellulose and the dispersant is methyl amyl alcohol.
[0050] The bending strength of the TiN / SiC composite ceramics is 348MPa and the fracture toughness is 4.1MPa·m 1 / 2 .
[0051] Example 5
[0052] The same as Example 4, the only difference is that the carbon thermal reduction temperature in nitrogen atmosphere is 1350°C. The bending strength of the prepared TiN / SiC composite ceramic is 352MPa, and the fracture toughness is 4.0MPa·m 1 / 2 .
[0053] Example 6
[0054] The same as Example 4, the only difference is that the vacuum reaction infiltration temperature is 1650°C. The bending strength of the TiN / SiC composite ceramic is 343MPa, and the fracture toughness is 4.7MPa·m 1 / 2 .
[0055] Example 7
[0056] Step 1, using 50wt% of silicon carbide powder, 30wt% of carbon black and 20wt% of titanium dioxide powder as powder raw materials, ball-milling the silicon carbide powder, titanium dioxide powder and carbon black for 3h to fully mix them, placing the ball-milled powder raw materials in a stirring tank, adding 2wt% of a binder and 5wt% of a dispersant based on the total weight of the powder raw materials, and then adding 100% of deionized water based on the total weight of the powder raw materials, and continuously stirring for 60min to obtain a slurry;
[0057] Step 2: pour the obtained slurry into a mold, let it stand for 8 hours, freeze-dry it for 24 hours, and demold it to obtain a porous ceramic body;
[0058] Step 3, weighing the same weight of silicon powder as the porous ceramic body, pouring it into a graphite crucible and spreading it, placing the porous ceramic body on the spread silicon powder, and then weighing the same weight of silicon powder and spreading it on the porous ceramic body, so that the porous ceramic body is buried in the silicon powder; placing the graphite crucible in a vacuum carbon tube furnace, opening the air inlet valve and the exhaust valve, heating to 1500° C. in a flowing nitrogen atmosphere, and keeping it warm for 3 hours;
[0059] Step 4: After the insulation is completed, close the air inlet valve and the exhaust valve, open the vacuum valve and the vacuum pump, maintain the vacuum degree in the carbon tube furnace at 15Pa, heat to 1650°C, and keep warm for 60 minutes. After the insulation is completed, cool naturally to obtain the TiN / SiC composite ceramic material.
[0060] The purity of the silicon carbide powder is 97% and the particle size is 20 μm. The purity of the titanium dioxide powder is 98% and the particle size is 4 μm. The purity of the carbon black is 99% and the particle size is 10 μm. The binder is hydroxyethyl cellulose and the dispersant is ethanol.
[0061] The bending strength of the TiN / SiC composite ceramics is 372MPa and the fracture toughness is 4.8MPa·m 1 / 2 .
[0062] Example 8
[0063] The same as Example 7, the only difference is that the vacuum reaction infiltration temperature is 1700°C. The bending strength of the TiN / SiC composite ceramics is 366MPa, and the fracture toughness is 4.5MPa·m 1 / 2 .
[0064] Example 9
[0065] The same as Example 7, the only difference is that the carbon thermal reduction temperature in nitrogen atmosphere is 1450°C. The bending strength of the prepared TiN / SiC composite ceramic is 378MPa, and the fracture toughness is 4.7MPa·m 1 / 2 .
[0066] It can be seen from the above embodiments that the process of the present invention is simple and the process is easy to control. The TiN / SiC composite ceramic material is prepared by a one-step method combining carbon thermal reduction nitridation of TiO2 and reactive infiltration in a nitrogen atmosphere, thereby improving the preparation efficiency of the material; and the in-situ generated uniformly distributed high-strength TiN grains are efficiently enhanced and toughened for the reaction-sintered silicon carbide ceramics through the dispersion strengthening mechanism.
[0067] It should be noted that, for those skilled in the art, several improvements and modifications may be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing a TiN / SiC composite ceramic material, characterized in that: The following steps are involved: Step 1: Mix silicon carbide powder, carbon black, titanium dioxide powder, a binder and water to obtain a slurry; the mass ratio of the silicon carbide powder, carbon black and titanium dioxide powder is 45-65:25-35:10-20; Step 2, placing the slurry in a mold and letting it stand, drying it, and demolding it to obtain a porous ceramic body; Step 3: burying the porous ceramic body with silicon powder, and performing carbon thermal reduction nitridation at 1300-1500° C. in a flowing nitrogen atmosphere to obtain a TiN / SiC / C porous ceramic preform; Step 4: The TiN / SiC / C porous ceramic preform is kept at a temperature of 1600-1750° C. and a vacuum degree of 1-30 Pa to obtain a TiN / SiC composite ceramic material.
2. The preparation method according to claim 1, characterized in that: The particle size of the carbon black is 1-20 μm; the mass ratio of the silicon carbide powder, the carbon black and the titanium dioxide powder is 45-65:25-30:10-20.
3. The preparation method according to claim 2, characterized in that: The purity of the silicon carbide powder is above 85%, and the particle size is 5-40 μm; the purity of the titanium dioxide powder is above 90%, and the particle size is 1-10 μm.
4. The preparation method according to any one of claims 1 to 3, characterized in that The mass of the binder is 1-5% of the total mass of the silicon carbide powder, carbon black and titanium dioxide powder; and the slurry also contains a dispersant.
5. The preparation method according to claim 4, characterized in that: The binder is sodium hydroxymethylcellulose and / or hydroxyethylcellulose; the dispersant is one or more of ethanol, methylpentyl alcohol, polyethylene glycol and fatty acid polyethylene glycol ester.
6. The preparation method according to claim 5, characterized in that: In the step 1, silicon carbide powder, carbon black and titanium dioxide powder are firstly ball-milled and mixed, and then a binder, a dispersant and water are added, stirred and mixed to obtain a slurry.
7. The preparation method according to claim 5, characterized in that: In the step 2, the standing time is 7 to 9 hours, and the drying is performed by freeze drying or forced air drying.
8. The preparation method according to claim 5, characterized in that: In the step three, the amount of silicon powder used is twice the weight of the porous ceramic green body; and the time of the carbon thermal reduction nitridation is 2 to 10 hours.
9. The preparation method according to claim 5, characterized in that: In the step 4, the heat preservation time is 30 to 120 minutes, followed by natural cooling to obtain a TiN / SiC composite ceramic material.
10. The TiN / SiC composite ceramic material obtained by the preparation method according to any one of claims 1 to 9.